Hydrocarbons in soil and meltwater stream sediments near Artigas Antarctic Research Station: origin, sources and levels. Issue 3 (15th February 2018) - Rodríguez, Carolina; Iglesias, Karen; Bícego, Márcia C.; Taniguchi, Satie; Sasaki, Silvio Tarou; Kandratavicius, Noelia; Bueno, Carolina; Brugnoli, Ernesto; Venturini, Natalia
Abstract: Aliphatic and polycyclic aromatic hydrocarbons (AHs and PAHs) were investigated in soil and meltwater stream sediments near the Uruguayan Artigas Research Station (BCAA). Gas chromatography with flame ionization detection and gas chromatography mass spectrometry were used to determine the composition of AHs and PAHs, respectively. Total AH concentrations were in the range 0.57–2333 µg g -1, while total PAH concentrations were in the range 1.36–51 650 ng g -1 . Based on AH and PAH concentrations, sites in the service area and next to the boat storeroom are highly contaminated, while the other sites sampled have moderate to low contamination levels or are not impacted. High unresolved complex mixture concentrations indicate the occurrence of previous petrogenic contamination, but the dominance of low molecular weight and alkyl PAHs indicate recent oil introductions. Anthropogenic hydrocarbons dominate and are related to diesel fuel and organic residue combustion, fuel storage and boat traffic. Petrogenic contamination is relatively high, as at other Antarctic stations, but is restricted to the boat storeroom and the service area where the incinerator, the generator room and fuel tanks are located. Improvements made in fuel management procedures and the dismantling of the old fuel tanks will reduce the risk of diesel leaks and their impact on the environment near the BCAA. This study provides reference information for future environmental monitoring.